Post-Traumatic Play in Child Victims of Adverse Childhood Experiences: A Pilot Study with the MCAST-Manchester Child Attachment Story Task and the Coding of PTCP Markers - Daniela D'Elia; Luna Carpinelli; Giulia Savarese (MDPI AG, 2022)
Background: Play is among the most frequently observed distorted behaviors in victims of Adverse Childhood Experiences (ACEs). Terr's (1981) studies helped to describe this behavioral distortion as post-traumatic child's play (PTCP). This study aimed to evaluate whether child victims of Adverse Childhood Experiences (ACEs) engaging in semi-structured play present the markers of post-traumatic child's play (PTCP) during the administration of the Manchester Child Attachment Story Task (MCAST), whose playful stories activate the attachment system. Methods: The sample comprised 17 child victims of ACEs (mean age = 6.76). Children were evaluated using the Manchester Child Attachment Story Task. Results: The analysis of the play clearly revealed the presence of markers associated with the characteristics of the post-traumatic play described by Terr (1981), namely, repetition, revisiting, hyperarousal, and danger. In particular, the intrusiveness dimension was observed, which can be identified in the post-traumatic play by the presence of recurrent memories, dreams, and dissociative symptoms. Conclusions: Post-traumatic play is characterized by repetition, containing aspects, scenes, or sequences of the traumatic event, expressed explicitly or symbolically.